Unravelling a mystery of hypokalemic hypertension- a rare case report of a reninoma - N.S.W Pathirana; P Dissanayake; S Pathmanathan; M.R Sumanatilleke; M.D.U Eranthaka; D.A Herath; T.M Samarasinghe; A.D.P Athukorala (BMC Endocrine Disorders)
Abstract Background Reninoma is a rare cause of secondary hypertension, which can be cured with surgery if identified early before any target organ damage occurs. It leads to hypokalaemia and hypertension and typically responds well to treatment with renin–angiotensin–aldosterone system blockers. However, confirmation of the diagnosis and the localisation of this rare culprit lesion can be challenging. Case presentation We describe a case of young-onset hypertension in a 19-year-old girl due to a reninoma. She had resistant hypertension with marked hypokalaemia, which required exceedingly high doses of potassium supplements. Biochemical Investigations revealed secondary hyperaldosteronism. Thus, she underwent a renal angiogram to exclude a renovascular cause for her hypertension. While the renal artery anatomy was normal, there was an exophytic renal lesion in the lower pole of the left kidney. Hence, the diagnosis of a reninoma was suspected. She underwent renal vein sampling to confirm the functionality of the detected tumour, but the results were inconclusive. After a multidisciplinary discussion, based on the clinical evidence, the renal lesion was thought to be a reninoma and a partial nephrectomy was done, removing the lesion. Immediately following resection, her blood pressure and potassium normalised without further drug treatment, and the resected lesion was later confirmed to be a reninoma by histopathological examination. Conclusion In young people with hypokalemic hypertension, reninoma should be considered when the more common causes are excluded since prompt treatment with excision of the culprit lesion can cure hypertension and prevent associated morbidity and mortality.